2022
DOI: 10.1002/jcla.24791
|View full text |Cite
|
Sign up to set email alerts
|

Application of lncRNAmiRNAmRNA ceRNA network analysis in the treatment of androgenic alopecia

Abstract: Background Long noncoding RNAs (lncRNAs) can be used as competitive endogenous RNAs (ceRNAs) to bind to microRNAs (miRNAs) to regulate gene expression. Previous studies have demonstrated that ceRNAs play an important role in the development of tumors. However, it is not clear whether the lncRNA–miRNA–mRNA ceRNA network plays a role in androgenic alopecia (AGA). Methods The hair follicles of three AGA patients and three healthy individuals were collected for high‐throughput whole transcriptome sequencing to scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…MiR-149-5p could induce hair follicle stem cell differentiation in goats by promoting the expression of β-catenin [30]. In addition, many studies also revealed the regulation relationship of miRNA-lncRNA-mRNA in hair follicle development [31][32][33]. APA is a kind of posttranscriptional process that could change the binding site of miRNA and mRNA [34].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-149-5p could induce hair follicle stem cell differentiation in goats by promoting the expression of β-catenin [30]. In addition, many studies also revealed the regulation relationship of miRNA-lncRNA-mRNA in hair follicle development [31][32][33]. APA is a kind of posttranscriptional process that could change the binding site of miRNA and mRNA [34].…”
Section: Discussionmentioning
confidence: 99%